The epidemiology of emergency presentations for falls across Western Victoria, Australia. (December 2019) - Holloway-Kew, Kara L.; Baker, Tim R.; Sajjad, Muhammad A.; Kotowicz, Mark A.; Livingston, Patricia M.; Khasraw, Mustafa; Hakkennes, Sharon; Dunning, Trisha L.; Brumby, Susan; Page, Richard S.; Sutherland, Alasdair; Venkatesh, Svetha; et al.
Abstract: Background: In order to develop and implement prevention strategies for falls, comprehensive epidemiological data are required. Therefore, this study mapped emergency presentations for falls across the western region of Victoria, Australia, encompassing urban, regional and rural areas. Methods: This cross-sectional study utilised electronic data for emergency presentations following a fall from <1 m for individuals aged ≥40 yr during 2014–2016 inclusive. Age-standardised incidence rates (per 1000 population/year) were calculated for each Local Government Area (LGA). Results: Age-standardised falls incidence varied across the LGAs, with the lowest occurring in the Rural City of Ararat LGA (4.4; 95%CI:3.5–5.4) and the highest for the City of Warrnambool (25.1; 95%CI:23.7–26.6), Colac-Otway (24.7; 95%CI:23.0–26.4) and Moyne (23.0; 95%CI:21.2–24.8). Patterns were similar for men and women when stratified by sex across these LGAs. For men and women combined, most patients arrived at the hospital using private transportation (55.3%) or road ambulance service (43.1%). Most falls occurred during leisure activities (48.0%) in a home setting (54.8%). Conclusions: Higher rates of falls presentations were observed in southern LGAs and most commonly occurred at home, during leisure activity. Future research should identify specific intervention strategies to reduce falls in the region, based on the data reported from this study.